Improved Protein Identification through the Use of Unstained Gels - Loiselle, D.R.; Thelin, W.R.; Parker, C.E.; Dicheva, N.D.; Kesner, B.A.; Mocanu, V.; Wang, F.; Wang, F.; Esteban Warren, M.R.; Borchers, C.H.
In this work, a method for improved protein identification of low-abundance proteins using unstained gels, in combination with robotics and matrix-assisted laser desorption/ionization tandem mass spectrometry, has been developed and evaluated. Omitting the silverstaining process resulted in increased protein identification scores, an increase in the number of peptides observed in the MALDI mass spectrum, and improved quality of the tandem mass spectrometry data.
Keywords: UNSTAINED GELS; PROTEIN IDENTIFICATION; PAGE; SILVER STAINING; IMMUNOPRECIPITATION; ROBOTICS; AUTOMATION; MALDIMS